2024
DOI: 10.1186/s42238-023-00208-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of social media compliance with cannabis advertising regulations: evidence from recreational dispensaries in Illinois 1-year post-legalization

Samantha Marinello,
Rebecca Valek,
Lisa M. Powell

Abstract: Background In the USA, an increasing number of states have legalized commercial recreational cannabis markets, allowing a private industry to sell cannabis to those 21 and older at retail locations known as dispensaries. Research on tobacco and alcohol suggests this new industry will use aggressive marketing tactics to attract new users and promote greater intensity of use. Of concern is that cannabis company advertising campaigns may be appealing to youth, promote false or misleading health cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Given the current federal illegal status of cannabis, there are no federallevel cannabis marketing policies, and state and local-level policies related to cannabis advertising restrictions vary significantly. [37][38][39] Further, compliance with such restrictions has been found to be low, 10,[40][41][42] and most restrictions do not apply to hemp-derived cannabis products which are rapidly gaining popularity. 43 The lack of effective marketing restrictions on cannabis products may explain our finding that e-cigarette marketing exposure through many channels was positively associated with sole-cannabis vaping.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the current federal illegal status of cannabis, there are no federallevel cannabis marketing policies, and state and local-level policies related to cannabis advertising restrictions vary significantly. [37][38][39] Further, compliance with such restrictions has been found to be low, 10,[40][41][42] and most restrictions do not apply to hemp-derived cannabis products which are rapidly gaining popularity. 43 The lack of effective marketing restrictions on cannabis products may explain our finding that e-cigarette marketing exposure through many channels was positively associated with sole-cannabis vaping.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, e-cigarette or vape products with nicotine, have become one of the most commonly used tobacco products in the U.S. The prevalence of past 30-day e-cigarette use with nicotine (or vaping nicotine) was 17.0% among middle and high school-aged youth in 2023 1 and 17.2% and 5.2% among young adults (ages [19][20][21][22][23][24][25][26][27][28][29][30] and midlife adults (ages [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], respectively, in 2022. 2 During the same time, many states legalized non-medical (or recreational) cannabis retail, coinciding with increased vape product use with cannabis (often called vaping cannabis or vape pens).…”
Section: Introductionmentioning
confidence: 99%
“…Commercialization may be more likely to impact use through these channels; in the open, it may be easier for companies to innovate methods of production to reduce costs, develop new products that may be more appealing and addictive, and engage in marketing and advertising. Some studies have found cannabis marketing increases in intensity over time (Marinello, 2024) and contains content that may be appealing to youth (Cao et al, 2020;Marinello et al, 2024;Shi & Pacula, 2021).…”
Section: Discussionmentioning
confidence: 99%